Factors affecting performance among managerial employees at Majlis Perbandaran Kulai (MPKu) / Nur Hayatunnisaa’ Wakimin and Nurulnadia Ahmad - Wakimin, Nur Hayatunnisaa’; Ahmad, Nurulnadia (2014)
Job performance is the important thing that each organization should take consideration seriously. This is because performance will give much impact to the outcome and directly toward the organization performance. Thus, this study is about the employee motivation, communication and job satisfaction towards job performance in Majlis Perbandaran Kulai (MPKu). It studied about the managerial employee’s performance in MPKu. It will cover three main ideas which is most related with employee problem such as motivation, communication and job satisfaction. Researchers want to study what the problem face by the employees regarded their performance in MPKu. Based on the interview between the researchers and some of the MPKu’s staff, they complained which are not satisfied with the division of labor in which the work tasked to them more than other employees in the same level and position. Besides that, disciplinary problems among lower level employees are troubling, especially in the case of early in the morning during breakfast time and they also absent from work after lunch hour until the end of office hour. This might happened due to the lack of work motivation, lack of good communication between employer and their employees, decrease in job satisfaction among employees which resulted in poor work performance and give a big impact to the organization and give a bad impression to the public authorities.